MENINGKATKAN HASIL BELAJAR IPS MATERI KELANGGKAAN SUMBER DAYA EKONOMI MELALUI MODEL PEMBELAJARAN KUANTUM PADA SISWA KELAS VIIIA SMP NEGERI 2 JARO TAHUN PELAJARAN 2012-2013 - Mutmainah Muthmainah (JURNAL SOCIUS, 2016)
Study achievement of Social Science The rare of low economic resource item . The purpose of the research is to describe the using quantum learning model  to increase students achievement and students’ responses to the rare of economic resource item class VIII A of SMP Negeri 2 Jaro. This research is research class action. In this research, there are begin by planning, class action, and reflection. There are two steps (cycles) in this research. The sample in this research is Class VIII A with 20 students; 9 boys, and 11 girls. The research was began 16 july up to 30 November 2012.  The result of this research shown that 1) Quantum Learning model can increase study achievement of social science the rare of economic resource class VIIIA SMP Negeri 2 Jaro with good achievement, 2) the applying of Quantum model not only in the process but also in the result can be increased,especially the students class VIIIA of SMP Negeri 2 Jaro. It is because there are relationships the characteristic of quantum learning with the purpose of social science at SMP. And  3) the applying of Quantum model  can increase positive responses to to the students while in the teaching and learning process. The all affects are to the students’ activity which active and communicative in teaching and learning process. The researcher suggest that the teacher of social science especially economic science should using Quantum Learning model to increase students’ achievement. To the teacher who wants applying Quantum Learning model in the classes should understand the basics of quantum and act as quantum. To fix and increase students’ responses are hopely to the teacher  while in the teaching and learning process use the method, model which is attractive and flexible. Keywords: study achievement, the Rare of the Economic Resource Item, Quantum Learning Model.